Development of light absorptive polymeric form stable composite phase change material for thermal storage - Kee, Shin Yiing (2018)
Thermal energy storage (TES) are utilized when there is a mismatch between thermal energy supply and energy demand. Among all TES, phase change material (PCM) is popular because it has a high thermal storage density with a small temperature variation during phase change process. However, the practical applications of PCM as TES face two major issues: volume change during phase change process and lack of study on light absorption of PCM which can convert light energy into thermal energy. Therefore, the development of a new light absorptive polymeric form stable composite phase change material is proposed to improve is thermal stability and light absorption ability over phase change process. In this study, light absorptive polymeric form stable composite phase change material was prepared using solution blending and dip coating method. Myristic acid (MA) was used as PCM to store latent heat; Polymer coating was used to contain the PCM; reduced graphene oxide (RGO) was incorporated into the polymer coating as light absorption materials. This study was carried out in three phases. First phase is to apply polyacrylic (PA) and silicone conformal coatings on composite PCM (MA/PMMA) with different weight percentage of MA to determine which coating is suitable to be used as polymer coating. Leakage test result showed that PA coating performed better in preventing leakage. However, adding PA coating and PMMA supporting material on PCM reduced latent heat significantly as the latent heat for coated PCM (MA/PMMA) in 60:40 wt% had low latent heat which was 91.42±7.22 J/g. Second phase is continued by maximizing the latent heat of PCM by directly applying different combination of PA and nitrile butadiene rubber (NBR) on MA pellet without PMMA supporting material. NBR was used in this phase because it was elastic to withstand the expansion during phase change process. The result showed that PANBR/MA pellet with 1-layer NBR (inner layer) and 1-layer PA (outer layer) was thermally stable and the melting latent heat was increased from 91.42±7.22 J/g to 131.84±5.76 J/g. Third phase is to improve light absorption of PANBR/MA pellet by adding RGO. RGO-PANBR/MA pellet with 1.5 wt% RGO loading had the highest amount of stored heat energy which was 48.91% higher than pellet without RGO. The average solar energy conversion of 1.5 wt% RGO-PANBR/MA pellet was about 21%. The melting point and latent heat of 1.5 wt% RGO-PANBR/MA pellet were 54.79±0.07 ºC and 119.91±6.67 J/g, respectively. All the above results showed that 1.5 wt% RGO-PANBR/MA pellet has potential to be used as light absorption thermal energy storage.